Implementation of Motivational Interviewing Techniques on the Spirit of Learning to Recite Al-qur’an Santri Pondok Pesantren Kyai Syarifuddin Maqoman Mahmuda Dormitory - Rohmah, Shofiatur (Risalatuna Journal of Pesantren Studies, 2025)
This article explores a counseling technique designed to assist, guide, and motivate clients to explore and overcome behavioral challenges through a method known as Motivational Interviewing (MI). Specifically, the study investigates its application to students (santri) at Pondok Pesantren Kyai Syarifuddin, Maqoman Mahmuda dormitory, who exhibit low enthusiasm in engaging with Qur’anic learning activities. The purpose of this study is to examine the implementation process and outcomes of the motivational interviewing technique in enhancing students' motivation to learn and recite the Qur’an. The research addresses the implementation process of motivational interviewing and identifies the resulting changes in students’ learning motivation at the Maqoman Mahmuda dormitory of Pondok Pesantren Kyai Syarifuddin. This study adopts a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, direct observation, and document analysis. The findings reveal that the implementation of motivational interviewing involves four key components: expressing empathy, developing discrepancy, accepting resistance, and supporting self-efficacy. As a result, students showed greater trust and confidence in their instructor, increased motivation inspired by external role models, stronger belief in their ability to succeed and achieve positive change, enhanced focus in Qur’anic learning, clearer learning goals, and self-driven change without coercion.